Understanding Membrane Fouling during the Clarification of Pomegranate Juice after Egg Albumin Pretreatment: An Analysis Using Hermia’s Empirical Models - Samreen; Satyanarayana, Ch V V; Edukondalu, L; Beera, Vimala; Rao, V Srinivasa (Food Science and Agriculture: Research Highlights Vol. 1, 2025)
Pomegranate (Punica granatum L., Punicaceae) is a popular tropical non-citrus fruit known for its attractive aroma, refreshing flavor, and favorable Brix/acid ratio. This juice is commonly used in fruit-based beverages, either alone or mixed with other fruit juices. The introduction of membrane processing enables the production of additive-free juices with high quality and a natural fresh-like taste. There have been a few studies on membrane filtration in fruit juice processing. Therefore, the present study investigated membrane fouling during the clarification of pomegranate juice after pretreatment with egg albumin. Pomegranates of the (cv. Ganesh) variety, sourced from the local market in Bapatla, Guntur District, Andhra Pradesh, were chosen for their high juice yield preferred by many juice processors and vendors. Hermia’s empirical models were applied to evaluate the fouling phenomena in microfiltration (MF) and ultrafiltration (UF) of pomegranate juice. The flux data was fitted into existing fouling models to elucidate the fouling mechanisms during membrane processing. For each mechanism, a mathematical model has been developed to predict a decline in permeate flux and its limiting value due to fouling. The coefficient of determination (R²) values for the gel layer model ranged from 0.804 to 0.977 for the 0.2 µm pore size membrane when filtering pomegranate juice. These R² values suggest intermediate pore blocking followed by gel layer formation. It was observed that a gel layer formed upon prolonged duration of MF with pomegranate juice. Poor-fitting was observed for the SPB (Sieving Porosity Model) and CPB (Cake Porosity Model) models.